Percepciones y prácticas tecnológicas para el desarrollo de la Competencia en Comunicación Lingüística. Un estudio de caso (Revista Lusófona de Educação, 2026)
Perceptions and technological practices for the development of Linguistic Communication Competence. A case studyAbstract: Competence in Linguistic Communication (CLC) is fundamental to students’ academic, personal and social development. In this context, Information and Communication Technologies (ICT) are presented as resources for strengthening this competence through the development of linguistic skills. The main objective was to analyse teachers’ perceptions and practices in relation to the use of ICT for the development of LCC. A quantitative, non-experimental and correlational approach was applied using a validated questionnaire to nine primary school teachers in Cadiz. Descriptive analyses and statistical tests such as Spearman and Mann-Whitney U were used. The results show that teachers perceive ICT as motivational tools, but they present some limitations such as lack of time and training. In addition, they show greater use of ICT to develop oral skills, with more notable integration among female teachers and teachers of language subjects. In conclusion, despite the positive assessment, the application of ICT for the development of CCL is uneven, highlighting the need for teacher training that promotes its use in all curricular areas.Keywords: linguistic communication competence, teachers, perceptions, practices, technologies.